Linguistic Swearing of Mobile Legend Players: A Pragmatic Study - Ellamae Alamo; Jay-Ar Benosa; Christian Fernandez; Mark Philip Paderan (Journal of English Education and Linguistics, 2023)
Swearing has traditionally been considered an inappropriate use of language, but numerous people continue to swear in formal and informal circumstances, like a mobile legend player. The presence of swear words in different societies and languages shows that this intriguing and multifarious language phenomenon has been prevalent in real-life discourse (Dynel, 2012). The study investigated the uses and meanings of mobile legend players' swearing behavior in Ghost Wreckers content videos. The transcription was run through Antconc, which also served as the main instrument of the study as it is mainly used in Corpus Linguistics. In the data analysis, numerous swear words were discovered in the game, which appeared to be influenced by the opponents and by the nature of the game. Ultimately, this investigation illustrates that swearing is not always unpleasant but also linguistically meaningful. Likewise, mobile legend players swearing behavior tend to perform various pragmatic functions to express emotions descriptively, abusively, cathartically, emphatically, and idiomatically. This data cements the idea that Mobile Legend is a competitive online game that stimulates raging emotions, a high level of competitiveness, and a firm hold on players' focus that causes them to express their excitement, frustrations, and joy during a game.